1849 NY Laws 403, ch. 278, § 1 - (:unkn) unknown (General Publisher, 1849)
Prohibited the manufacture, sale, giving, or disposing of any instrument or weapon usually known as a slungshot, and prohibited the carrying any slungshot or similar weapon. Violators guilty of misdemeanor, punishable by fine not less than two hundred and fifty, nor over five hundred dollars, or imprisonment not less than six months, nor over two years.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - NON-GUN ARMS